Making the world safe for democracy : a century of Wilsonianism and its totalitarian challengers - Perlmutter, Amos (Univ. of North Carolina Press, 1997)
In this interpretive study, Amos Perlmutter offers a comparative analysis of the three most significant world orders of the twentieth century: Wilsonianism, Soviet Communism, and Nazism. Anchored in three hegemonial states - the United States, the Soviet Union, and Nazi Germany - these systems, he finds, shared certain characteristics that distinguished them from other attempts to restructure the international political scene. While Communism and Nazism were committed to imperial ideologies, Wilsonianism was inspired by an exceptionalist, peaceful, democratic, and free market world order. But all three were able to mobilize industrial, technological, and military resources in pursuing their goals. In the process of examining the democratic, Communist, and Nazi systems, Perlmutter also provides a framework for understanding U.S. foreign policy over the course of the century, particularly during the Cold War. He underscores the importance of ideology in establishing an international order, arguing that in the wake of the Soviet Union's demise, no system - not even Wilsonianism - can lay claim to the title of new world order.